Erythropoietin Protects Against Lipopolysaccharide-Induced Microgliosis and Abnormal Granule Cell Development in the Ovine Fetal Cerebellum - McDougall, Annie R. A.; Hale, Nadia; Rees, Sandra; Harding, Richard; De Matteo, Robert; Hooper, Stuart B.; Tolcos, Mary (Frontiers in Cellular Neuroscience, 2017)
Erythropoietin (EPO) ameliorates inflammation-induced injury in cerebral white matter. However, effects of inflammation on the cerebellum and neuroprotective effects of EPO are unknown. Our aims were to determine (i) whether lipopolysaccharide (LPS)-induced intrauterine inflammation causes injury to, and/or impairs development of the cerebellum and (ii) whether recombinant human EPO (rhEPO) mitigates these changes. At 107±1 days’ gestational age (DGA; ~0.7 of term), fetal sheep received LPS (~0.9μg/kg; i.v) or an equivalent volume of saline, followed 1h later with 5000IU/kg rhEPO (i.v) or an equivalent volume of saline (i.v). This generated the following experimental groups: control (saline + saline; n=6), LPS (LPS + saline, n=8) and LPS + rhEPO (n=8). At necropsy (116±1 DGA; ~0.8 of term) the brain was perfusion-fixed and stained histologically (H&E) and immunostained to identify granule cells (NeuN), granule cell proliferation (Ki67), Bergmann glia (GFAP), astrogliosis (GFAP) and microgliosis (Iba-1). In comparison to controls, LPS fetuses had an increased density of Iba-1-positive microglia (p<0.005) in the lobular white matter; rhEPO prevented this increase (p<0.05). The thickness of both the proliferative (Ki67-positive) and post-mitotic zones (Ki67-negative) were increased in LPS-exposed fetuses compared to controls (p<0.05), but were not different between controls and LPS+rhEPO fetuses. LPS also increased (p<0.001) the density of granule cells (NeuN-positive) in the internal granule layer (IGL); rhEPO prevented the increase (p<0.01). There was no difference between groups in the areas of the vermis (total cross-section), molecular layer (ML), IGL or white matter (WM), the density of NeuN-positive granule cells in the ML, the linear density of Bergmann glial fibres, the areal density or somal area of the Purkinje cells, the areal coverage of GFAP-positive astrocytes in the lobular and deep WM, the density of Iba-1-positive microglia in the deep WM or the density of apopotic cells in the cerebellum. LPS-induced intrauterine inflammation caused microgliosis and abnormal development of granule cells. rhEPO ameliorated these changes, suggesting that it is neuroprotective against LPS-induced inflammatory effects in the cerebellum.